Family-based therapy for adolescents with suicidal behavior - Ati, Niken Asih Laras; Kurian , Midhu (PT Saintek Medika Nusantara, 2022)
Suicide behavior in adolescents is a global phenomenon in all countries. Family is a causal factor and a protective factor for suicidal behavior in adolescents so that therapy given to adolescents with suicidal behavior must involve the family. This systematic review aimed to determine what family-based therapy can be given to adolescents with suicidal behavior. Systematic review began by identifying research articles in two databases, Proquest and EBSCO, 2013 – 2018, with predetermined keywords. The articles obtained were selected according to the inclusion and exclusion criteria specified. Five articles matched the inclusion and exclusion criteria. Based on the analysis results, family therapy for adolescents with suicidal behavior can be grouped based on providing educational information and parenting strategies, changing behavior, increasing family attachment, and preventing suicide in adolescents. Several therapeutic methods can be given to families who have teenagers with suicidal behavior. This article can be a reference in providing family-based therapy for adolescents with suicidal behavior.